Multilayered, Hyaluronic Acid‐Based Hydrogel Formulations Suitable for Automated 3D High Throughput Drug Screening of Cancer‐Stromal Cell Cocultures. Issue 11 (9th June 2015) - Engel, Brian J.; Constantinou, Pamela E.; Sablatura, Lindsey K.; Doty, Nathaniel J.; Carson, Daniel D.; Farach‐Carson, Mary C.; Harrington, Daniel A.; Zarembinski, Thomas I.
<x xml:space="preserve">Abstract</x> Validation of a high‐throughput compatible 3D hyaluronic acid hydrogel coculture of cancer cells with stromal cells. The multilayered hyaluronic acid hydrogels improve drug screening predictability as evaluated with a panel of clinically relevant chemotherapeutics in both prostate and endometrial cancer cell lines compared to 2D culture.